2007
DOI: 10.1016/s0929-6646(09)60251-5
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic-molecular Correlation in Early Mycosis Fungoides Using T-cell Receptor γ Gene Rearrangement by Polymerase Chain Reaction with Laser Capture Microdissection

Abstract: TCRgamma PCR allows the diagnosis of MF in patients with lymphocyte-poor lesions, suggestive of MF pathologically. TCRgamma PCR is more likely to be negative with moderate to severe inflammation, particularly with papillary dermal fibrosis. We suggest that the ratio of malignant clonal to reactive T-cells is critical for MF diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The sensitivity of TRG amplification within a lesion is influenced by the frequency of the neoplastic clone in the population of infiltrating cells and by the complexity of the associated polyclonal repertoire. The neoplastic clone needs to occur at a frequency of about 5–10% for detection to occur 21,22 . Also, minor clonal populations are at greater risk of going undetected if they involve frequently rearranged Vγ and Jγ segments, which will be lost amidst the polyclonal repertoire 22 …”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of TRG amplification within a lesion is influenced by the frequency of the neoplastic clone in the population of infiltrating cells and by the complexity of the associated polyclonal repertoire. The neoplastic clone needs to occur at a frequency of about 5–10% for detection to occur 21,22 . Also, minor clonal populations are at greater risk of going undetected if they involve frequently rearranged Vγ and Jγ segments, which will be lost amidst the polyclonal repertoire 22 …”
Section: Discussionmentioning
confidence: 99%
“…The positive rate of TCR-γ gene rearrangement in early MF suspected cases was reported to be 40% to 71%[6],[7], which is useful for early diagnosis. Stevens et al [17] conducted logistic regression analysis on some clinical and laboratory data and established a simple clinical scoring system to facilitate MF diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, malignant cells tend to localize to the epidermis 11 -13 and in Pautrier collections. 14 Our case adds to the few reported instances in which microdissection has been used in the diagnosis of unusual or rare types of T-cell lymphoma 15 and is the first reported use of microdissection to identify a monoclonal proliferation in a case of suspected SPTCL. This technique may be useful to better characterize those patients with a clinical and histopathologic overlap between panniculitis and lymphoma.…”
Section: Discussionmentioning
confidence: 62%
“…Case series ranging from 5–29 cases have shown that microdissection can improve sensitivity of detection, particularly in early patch stage mycosis fungoides. In this context, malignant cells tend to localize to the epidermis 11–13 and in Pautrier collections 14 …”
Section: Discussionmentioning
confidence: 99%